Implementasi Integrasi Keilmuan di UIN Salatiga - Farida Hanun (Badan Litbang dan Diklat Kementerian Agama RI, 2023)
This study aims to determine the implementation of the concept of scientific integration at UIN Salatiga. The research was conducted with a qualitative method. Collecting research data through interviews and documentation studies. The research informants were the Chancellor, Deputy Chancellor I for Academic and Cooperation Affairs, Dean of the Tarbiyah Faculty, Quality Assurance Institute, Lecturers and Students.Â The results of the study show: (a) The Circle of Wasathiyah Knowledge's concept of scientific integration is published in the form of academic manuscript documents, (b)The strategy for implementing scientific integration at UIN Salatiga is through: learning, research and community service, (c) The curriculum at the study program level does not have specific subjects related to scientific integration, but is directly implicitly included in the implementation of learning in the classroom, and scientific integration can be seen in the lesson plans for their subjects, (d) Supporting factors: Lecturer human resources and adequate infrastructure, the concept of scientific integration is developing and the availability of science-based study programs. While the inhibiting factors: not all lecturers have sufficient insight into Scientific Integration, the backgrounds of students are diverse, there are no guidelines for implementing scientific integration at UIN Salatiga.